Effect of accumulated Stomach Gas due to Positive Pressure Ventilation in Children on Oximetery Values - Syed Hamid Ali Shah, Syed Hamid Ali Shah; Muhammad Mubeen, Muhammad Mubeen; Mushtaq Hussain Raja, Mushtaq Hussain Raja; Syed Zulfiqar Haider, Syed Zulfiqar Haider; Shadab Ahmed Butt, Shadab Ahmed Butt; Muhammad Manzoor, Muhammad Manzoor (Journal of Rawalpindi Medical College, 2007)
stomach gas in children, undergoing positive pressure ventilation with face mask, helps in improving the arterial oxygen saturation. Methods: This was a quasi-experimental study whose procedures were performed at Combined Military Hospital, Lahore and Mardan, from May 2005 to Nov 2006. Fifty children scheduled for surgery were included. Age range of patients was between 06 months to 02 years. Patient status was American Society of Anaesthesiologists I and II. All were ‘nil by mouth’ for the past 4-6 hours. In 25 cases undergoing positive pressure ventilation, the stomach gas was removed by nasogastric tube (Group A). In the other 25 cases the stomach gas was not removed (Group B). Oximetery was done during the conduct of anaesthesia. Average value of each case was determined and the data compared and analyzed. Results: 80% of patients in whom stomach gas was removed showed 100% oxygen saturation (SPO2) and the remaining 20% patients had 99% saturation. Whereas the group in which stomach gas was not removed, 48% patients showed 100% saturation, 32% patients had 99% and 20% patients had 98% oxygen saturation. Conclusion: Positive pressure ventilation with face mask in children can cause gaseous distension of the stomach. Removal of this gas can help improve the oxygen saturation.